The Role of Motivation and Professional Competence in Improving Teacher Performance - Muhammad Fachmi; Mustafa Mustafa; Ali Murdhani Ngandoh (Journal of Digital Learning and Education, 2021)
Abstract: This study aims to analyze the role of work motivation and professional competence in improving the performance of Vocational High School teachers in Soppeng Regency, as well as which variables are most dominant in influencing the improvement of teacher performance. Researchers took a sample of 72 teachers from five vocational schools in Soppeng Regency with the sampling technique, namely random sampling. The data analysis technique used is multiple linear regression analysis with SPSS software. The results showed that work motivation has a positive and significant effect on teacher performance, meaning that if the work motivation is higher, the teacher's performance will also increase. In addition, professional competence also has a positive and significant effect on teacher performance, so that if professional competence is getting better, teacher performance will also increase. Researchers also found that work motivation is the most dominant variable affecting the improvement of teacher performance in schools.